Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 122267 species occurrences available in GBIF matching the query: { "and" : [ "OccurrenceStatus is Present", "TaxonKey is Tursiops truncatus (Montagu, 1821)" ] } The dataset includes 122267 records from 694 constituent datasets: 43 records from SEFSC Mid-Atlantic Tursiops Survey, 1995 3. 9 records from UNCW Aerial Surveys for monitoring of proposed Onslow Bay USWTR site - Right side -. 9 records from Cetacean occurrence off the west central Portugal coast from boat-based surveys 2007-2008. 42 records from Virginia CZM Wind Energy Area Survey- Left side - November 2012 through April 2014. 5 records from NMNH Paleobiology Specimen Records. 683 records from BLM CETAP AIR Sightings. 5 records from Seasearch Marine Surveys in England. 26 records from Museum of Comparative Zoology, Harvard University. 460 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 11 records from SDNHM Mammology Collection. 3 records from Empire Wind Digital Aerial Wildlife Surveys for BOEM Lease Area OCS-A 0520, Equinor Wind US LLC, February - December 2019. 5 records from HRC CRC Small Vessel-Based Monitoring Surveys March-April 2006. 3 records from HRC Kaula Vessel-Based Monitoring Surveys June 2011. 24 records from Observations de mammifères marins du Réseau National d'Echouages en Métropole. 96 records from SWFSC Marine Mammal Survey, STAR 2003, Cruise 1624. 19 records from Parc_National_de_Port_Cros_2017_12_18. 1 records from FHSM Mammals Collection. 1 records from Programme delphinidés 2007-2010 à Mayotte. 12 records from SEUS Right Whale EWS Aerial Surveys 2017-18. 2070 records from Tethys Research Institute shipboard survey cetacean sightings 1986-2012. 3 records from University of Florida Vertebrate Paleontology. 16 records from CODA cetacean sightings on tracker platform of vessel surveys 2007. 10 records from UNCW JAX Aerial Survey - Left side - 2015. 8 records from UNCW PAX Aerial Survey - Left side - 2016. 6396 records from Sarasota Dolphin Research Program Bottlenose Sightings 1971-2009. 83 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 592 records from Mingan Island Cetacean Study 84-07. 736 records from CIRCE Marine mammals off Spain 2001-2012. 1087 records from Observatoire Pelagis - Reseau National Echouage (French stranding network) strandings 1934-2018. 14 records from NEFSC Deepwater Marine Mammal 2002. 3 records from AMAPPS Northeast Aerial Cruise Spring 2014. 1 records from St Andrews BioBlitz 2015. 14 records from SWFSC Marine Mammal Survey, PODS 1993, Cruise 1508. 1 records from SEUS Right Whale EWS Aerial Surveys 2018-19. 7 records from AMAPPS Northeast Aerial Cruise Summer 2010. 78 records from SOCAL KB04, FZN1, FZN2 Marine Mammal Aerial Monitoring 2011-2012. 14 records from SCANS I cetacean sightings 1994. 14 records from OceanCare cetacean sightings in Sicily, Italy 2016-2019. 1 records from Logan City Council Species Sightings. 1 records from Steinhardt Museum of Natural History (SMNHTAU) Vertebrates. 17 records from Merseyside BioBank (verified). 163 records from BLM CETAP OPP Sightings. 17 records from CalCOFI marine mammal surveys 2004-2008 - on effort. 32 records from Actualización de la base de datos del estado de Morelos de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 82 records from MMS Ship survey, SCB 1975-1978. 4 records from UNCW Aerial Surveys for monitoring of proposed Onslow Bay USWTR site - Left side -. 541 records from INSDC Sequences. 49 records from USWTR Onslow Bay Aerial Survey -Right side- 2008-2010. 185 records from Marine mammal records of Cuba. 16 records from AMAPPS Northeast Aerial Cruise Spring 2019. 2 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores tuna fishery from 1998 to 2013: during the capture of live bait. 5 records from SWFSC Marine Mammal Survey, CalCurCEAS 2014, Cruise 1647. 20 records from SCANS II cetacean sightings on tracker platform of vessel surveys 2005. 126 records from Observations de Mammifères marins. Globice Réunion 2009-2013. 25 records from SWFSC Marine Mammal Survey, MOPS 1987, Cruise 1080. 10 records from Tasmanian Natural Values Atlas. 5 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 67 records from Macaulay Library Audio and Video Collection. 76 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 17 records from Parc_National_des_Calanques_2017_12_18. 1 records from ZUEC-MAM - Coleção de Mamíferos do Museu de Zoologia da UNICAMP. 122 records from Artportalen (Swedish Species Observation System). 122 records from Norwegian Species Observation Service. 33 records from UNCW Hatteras Aerial Survey - Right side - 2016. 18 records from Marine Mammals Observations - Total South Africa. 14 records from Virginia CZM Wind Energy Area Survey- Right side - January 2014 through March 2016. 1 records from UTEP Mammals (Arctos). 6 records from Données des réserves naturelles nationales gérées par la Ligue pour la protection des oiseaux (LPO). 2 records from HRC CRC Small Vessel-Based Monitoring Surveys December 2010. 6 records from RV Investigator Voyage IN2017_T01 Seabird Observations, Australia (2017). 1 records from Aerial Oil Spill Response Survey 1994-1997. 1 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 14 records from UNCW Hatteras Aerial Survey - Right side - 2015. 13 records from HRC CRC Kauai Small Vessel-Based Monitoring Surveys July-August 2011. 5665 records from The Dolphin Project. 15 records from AFAST Hatteras Aerial Survey -Right side- 2011-2012. 113 records from Acquario di Genova, Delfini Metropolitani Project, cetacean sightings 2001-2009. 1 records from HRC USWEX Aerial-Based Monitoring Surveys 2007. 8 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 2 records from Cetacean distribution around Mayotte Island. 19 records from MVZ Mammal Collection (Arctos). 1 records from Deep Panuke whale sightings 2003. 1 records from HRC Kaula Small Vessel-Based Monitoring Surveys February 2011. 15 records from Anymals+plants - Citizen Science Data. 18 records from DASSH Data Archive Centre volunteer sightings records. 65 records from Adriatic Shipping Company marine mammal sightings in the Adriatic Sea 1988-2000. 1 records from CRCM Vertebrate Collection. 26 records from Queensland Museum provider for OZCAM. 4 records from HRC CRC Small Vessel-Based Monitoring Surveys August 2007. 19 records from SCANS II cetacean sightings on primary platform of vessel surveys 2005. 2 records from TTU Mammals Collection. 37 records from International Barcode of Life project (iBOL). 8 records from MIRC PIFSC Small Vessel Surveys Jun-Aug 2013. 3 records from BRERC species records from all years at full resolution excluding Notable Species within the last 10 years. 23 records from UNCW Hatteras Aerial Survey -Right side- 2017. 16 records from UNCW Hatteras Aerial Survey - Left side - 2015. 3 records from Hatikka Observation Database. 4 records from MIRC PIFSC CNMI Vessel Surveys May-Jul 2012. 25 records from Données d'occurrences Espèces issues de l'inventaire des ZNIEFF. 180 records from NE Scotland marine mammal records 1800-2010. 55 records from SWFSC Marine Mammal Survey, Vaquita 2008, Cruise 1637. 62 records from Diveboard - Scuba diving citizen science observations. 67 records from USWTR JAX Aerial Survey -Left side- 2009-2010. 7 records from SWFSC Marine Mammal Survey, CSCAPE 2005, Cruise 1628. 356 records from UNCW Marine Mammal Sightings 2002. 51 records from Multi-species marine sighting survey in Golfo Dulce, Costa Rica, Jan-Feb 2010. 68 records from AMAPPS Southeast Shipboard Cruise Summer 2016. 601 records from UNCW Right Whale Aerial Survey 05-06. 53 records from AMNH Mammal Collections. 11 records from OceanCare cetacean sightings 2001-2014. 15 records from Données Mammifères marins Aquasearch - Dauphin Passion. 34 records from WildNet - Queensland Wildlife Data. 1 records from JAX SEASWITI Aerial Monitoring 2010. 29 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 15 records from HRC CRC Small Vessel-Based Monitoring Surveys June-July 2012. 4 records from HRC RIMPAC Vessel-Based Monitoring Surveys 2008. 3 records from Bernice P. Bishop Museum. 247 records from LACM Vertebrate Collection. 40 records from SEFSC GoMex Oceanic 1996. 65 records from USWTR Onslow Bay Aerial Survey -Left side- 2008-2010. 47 records from SEFSC Mid-Atlantic Tursiops Survey, 1995 2. 84 records from Red Sea Cetacean Review - Sightings. 134 records from Observation Cétacés du projet Grand Dauphin Étude et Gestion en Méditerranée. 1 records from Green Balkans cetacean strandings on the Bulgarian Black Sea coast. 9 records from Happywhale - Common Bottlenose Dolphin in South Pacific Ocean. 7 records from Registro de varamientos/mortalidad de fauna marino-costera en Ecuador continental para el periodo 2015 - 2020. 9 records from UNCW JAX Aerial Survey - Left side - 2016. 369 records from walvisstrandingen_nl. 2 records from Monitoring of the effects of Belgian wind mill parks on benthic macro-invertebrates and the fish fauna of soft substrates - reference situation. (WINMON). 10 records from Données d'observation de la mégafaune marine issues des campagnes océanographiques en France métropolitaine. 1 records from University of California Museum of Paleontology. 9 records from Israel Nature and Parks Authority. 1 records from Acoustic detections from research cruises in the Med sea, 1994-2001. 770 records from Observatoire Pelagis aerial surveys 2002-2019. 95 records from AMAPPS Northeast Shipboard Cruise Summer 2016. 577 records from Dreal Corse - Base Ogreva. 112 records from SWFSC Marine Mammal Survey, STAR 2006, Cruise 1630. 111 records from AMAPPS Southeast Aerial Cruise Spring 2012. 191 records from VACAPES NFC Aerial Surveys 2018-2019. 4 records from RNF - Données de l'association Vivarmor Nature. 34 records from Tethys Research Institute aerial survey cetacean sightings 2009-2011. 4 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 8 records from NEFSC Aerial Survey - Experimental 2002. 36 records from Virginia CZM Wind Energy Area Survey- Right side - November 2012 through April 2014. 1 records from Sightings for AN/AQS-20 Sonar Test Event - April-May 2013. 1 records from WNMU Mammal Collection (Arctos). 13 records from NSN Monitoring for Pier 1 Upgrades 2011-2012. 1 records from Monitoreo de peces arrecifales y tiburones parte de los valores objetos de conservación (VOC) en el santuario Malpelo para el año 2020. 682 records from Observations de Mammifères marins de 2006 à 2014 en Polynésie française. 7 records from HRC CRC Small Vessel-Based Monitoring Surveys June-July 2008. 226 records from SEFSC GoMMAPPS 2017 Summer Aerial Survey. 61 records from National Whale and Dolphin Sightings and Strandings Database. 1 records from Historical strandings of cetaceans on the Portuguese coast. 1 records from Lizard Island Research Station. 2 records from Application INPN Espèces: Observations naturalistes, participatives et opportunistes, fondées sur des photographies. 23 records from AMAPPS Northeast Aerial Cruise Spring 2012. 442 records from Oceanic Society's Marine Mammal Sightings in Belize 1992 - 2011. 604 records from Gray Whales Count annual survey of northbound migration in Santa Barbara Channel, California 2011-2012. 5 records from Bahamas Marine Mammal Research Organisation Strandings. 10 records from AMAPPS Northeast Aerial Cruise Winter 2017. 29 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 114 records from Observations opportunistes des Mammifères marins du lagon de la province Sud de Nouvelle-Calédonie par les agents de la direction de 2009 à 2013. 6 records from Records of protected animal, plant and fungi species in Ukraine. 7 records from Marine Fauna Observer data collected on board seismic survey vessels operating around Suriname as part of an EU-funded Marine Spatial Planning project. 38 records from Belgian Marine Mammals database. 17 records from Cetacean sightings off Turkey 2006-2011. 10 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 27 records from Observations de cétacés en Méditerranée par le Groupe d'étude des Cétacés de Méditerranée de 2012 à 2017. 418 records from UNCW Right Whale Aerial Surveys 2008. 886 records from Virginia Aquarium Marine Mammal Strandings 1988-2008. 237 records from NSW BioNet Atlas. 1 records from FBIP: SeaKeys_SANBI: Marine images iSpot_2013. 4 records from Census of the animals of Benin. 14 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (MZFC_FCMM). 11 records from SEFSC GoMMAPPS Vessel Survey 2018 Summer. 134 records from SEFSC Southeast Cetacean Aerial Survey 1995. 3 records from Cetacean and sea turtle sightings in Gabon. 4 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 188 records from Norfolk/VA Beach Bottlenose Dolphin Photo-ID Surveys. 19 records from Materials to the mammal atlas of Ukraine. 59 records from CalCOFI and NMFS Seabird and Marine Mammal Observation Data, 1987-2006. 16 records from MMS Surveys, SCB 1995-1997. 6 records from UNCW Norfolk Canyon Aerial Survey -Left side- 2017. 68 records from AMAPPS Southeast Aerial Cruise Fall 2016. 33 records from Distribution des Cétacés et Siréniens dans les eaux de Nouvelle-Calédonie. 37 records from AFTT Cape Hatteras Aerial Survey -Left side- 2014. 3 records from Mammalogy Collection - Royal Ontario Museum. 7 records from BOEM Sperm Whale Seismic Study (SWSS) S-Tag cetacean sightings 2002-2004. 6 records from Manx Biological Recording Partnership UNVERIFIED Isle of Man records between 14/02/2017 and 05/09/2019. 40 records from PIFSC Mariana Archipelago cetacean surveys 2010-2019. 7 records from Abundance and distribution of cetaceans in the state of Aragua, Venezuela. 7 records from SWFSC Marine Mammal Survey, CLAWS 2015, Cruise 1648. 8 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 106 records from Happywhale - Common Bottlenose Dolphin in North Pacific Ocean. 5 records from NEFSC Aerial Circle-Back Abundance Survey 2004. 1 records from Données naturalistes de François BRETON. 34 records from LSUMZ Mammals Collection. 17 records from USWTR Onslow Bay Aerial Survey -Left side- 2010-2011. 3 records from KYMA boat-based surveys in Thyrrhenian Sea and Ionian Sea. 137 records from NEFSC Right Whale Aerial Survey. 95 records from SEFSC Gomex Shelf 1994. 4 records from HRC CRC Small Vessel-Based Monitoring Surveys April-May 2008. 44 records from Bahamas Marine Mammal Research Organisation On-transect Sightings. 50 records from UNCW Aerial Survey 1998-1999. 1 records from UCLA Donald R. Dickey Bird and Mammal Collection. 1 records from HRC RIMPAC Vessel-Based Monitoring Surveys 2006. 2 records from MIRC Shore-Based Surveys March 2015. 95 records from Fauna Atlas N.T.. 23 records from SWFSC Marine Mammal Survey, MOPS 1989, Cruise 1268. 5 records from Opportunistic marine mammal sightings from commercial whale watching vessels, Montauk, New York 1981-1994. 56 records from Western Australian Museum provider for OZCAM. 8 records from Pelorus Sound / Te Hoiere (HS66) Hydrographic Survey Marine Mammal Observations. 42 records from UNCW Marine Mammal Sightings 1998-1999. 2 records from Marine Records from Pembrokeshire Marine Species Atlas. 11 records from USWTR Onslow Bay Aerial Survey -Right side- 2010-2011. 2 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 145 records from JNCC seabird distribution and abundance data (all trips) from ESAS database. 73 records from CNMA/Colección Nacional de mamíferos. 6 records from Collection Mammalia SMF. 3 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: MAMMALIA_FZ. 305 records from UNCW Marine Mammal Sightings 2001. 7 records from National Trust Species Records. 5 records from HRC CRC Small Vessel-Based Monitoring Surveys October 2009. 15 records from SWFSC Marine Mammal Survey, STAR-LITE 2007, Cruise 1634. 2 records from Australian National Wildlife Collection provider for OZCAM. 3 records from Species biodiversity transnational geo-database - IMPRECO Project. 1 records from Mamíferos, aves y peces de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 50 records from SWFSC Marine Mammal Survey, STAR 1998, Cruise 1610. 5 records from SWFSC Marine Mammal Survey, ORCAWALE 1996, Cruise 1604. 84 records from Cetacean diversity, distribution, and abundance in northern Veracruz, Mexico. 25 records from UNCW Hatteras Aerial Survey - Left side - 2016. 9 records from Asia-Pacific Dataset. 3 records from Sightings of marine mammals carried out during oceanographic surveys in the Argentine continental shelf. 2 records from NEFSC 1995 pe9502. 1 records from Fife Nature Records Centre combined dataset 2018/19. 133 records from Océanopolis mammifères marins en Bretagne 1993-2015. 2 records from HRC CRC Small Vessel-Based Monitoring Surveys December 2008. 1 records from Auckland Museum NZ Marine Collection. 15 records from Cybelle Méditerranée. Observation nautique avec effort d'observation. 27 records from Miscellaneous records held on the Cofnod database. 15 records from USWTR JAX Aerial Survey -Left side- 2010-2011. 45 records from NEFSC Survey 1998 1. 25 records from Base de datos de mamíferos de México depositados en colecciones de Estados Unidos y Canadá. 98 records from AMAPPS Southeast Aerial Cruise Summer 2016. 105 records from SWFSC Marine Mammal Survey, PODS 1992, Cruise 1468. 2 records from Happywhale - Common Bottlenose Dolphin in Indian Ocean. 13 records from Data on cetacean strandings on the Ukrainian coast of the Black Sea (2017). 1570 records from Bahamas Marine Mammal Research Organisation Opportunistic Sightings. 24 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 143 records from SWFSC Marine Mammal Survey, PODS 1993, Cruise 1509. 110 records from Australian Museum provider for OZCAM. 233 records from Prospections de cétacés par Globice - données historiques 2003-2017. 1 records from Cowan Tetrapod Collection - Mammals. 1352 records from Observation.org, Nature data from around the World. 36 records from Happywhale - Common Bottlenose Dolphin in North Atlantic Ocean. 973 records from Irish Whale and Dolphin Group. 38 records from AFTT Hatteras Aerial Survey -Right side- 2012-2013. 49 records from SWFSC Marine Mammal Survey, MOPS 1990, Cruise 1369. 12 records from Ghent University - Zoology Museum - Vertebrate collection. 6 records from Mammal records for Dumfries and Galloway. 7 records from Données Mammifères marins de Polynésie française de Te mana o te moana. 1 records from Universidad del Valle de Guatemala - Colecciones Biológicas - Mamíferos. 4 records from Current status of cetaceans in Aragua, Venezuela. 32 records from Cape Hatteras 04-05. 34 records from VACAPES Vessel Nearshore Humpback Whale Monitoring 2015-2019. 1103 records from Virginia and Maryland Sea Turtle Research and Conservation Initiative Aerial Survey Sightings, May 2011 through July 2013. 38 records from SWFSC Marine Mammal Survey, STAR 2006, Cruise 1631. 19 records from Jonian Dolphin Conservation di Taranto marine mammal sightings 2009-2012. 21 records from SEFSC Atlantic surveys 1992. 2 records from VACAPES FIREX and ASW Aerial Monitoring 2010. 4 records from Sargasso 2005 - cetacean sightings. 450 records from Alnitak-Alnilam Cetaceans and sea turtles surveys off Southern Spain. 61 records from Aerial Survey Baseline Monitoring in the Continental Shelf Region of the VACAPES OPAREA: January 2016 - December 2016 (right side). 301 records from BLM CETAP SHIP Sightings. 13 records from CalCOFI marine mammal surveys 2004-2008 - off effort. 327 records from CE.TU.S. research cetacean sightings in the North Tuscany and Tuscan Archipelago waters, 1997-2011. 74 records from SEFSC Atlantic surveys 1999. 1 records from HRC RIMPAC Aerial-Based Monitoring Surveys 2008. 58 records from SWFSC Marine Mammal Survey, MOPS 1987, Cruise 1081. 46 records from AFTT Hatteras Aerial Survey -Left side- 2012-2013. 4 records from NYSM Mammals. 2 records from Mammal specimen database of Kanagawa Prefectural Museum of Natural History. 1 records from Sightings for Airborne Mine Neutralization System Vessel Monitoring in the NSWC PCD Study Area from December 2011. 1 records from UConn Mammals. 46 records from SEFSC Gomex Shelf 2000. 143 records from VACAPES Offshore Study Area Observations 2015-2018. 17 records from Observation de Cétacés en Méditerranée 1995-2011- EcoOcéan Institut. 27 records from SWFSC Marine Mammal Survey, MOPS 1986, Cruise 0990. 1 records from Données naturalistes hors Île-de-France saisies dans Cettia-idf. 70 records from DUML vessel-based line transect surveys for proposed Onslow Bay USWTR site 2007-2010. 2 records from HSU Vertebrate Museum Mammals Collection. 4 records from Naturalis Biodiversity Center (NL) - Vermes. 57 records from SEFSC Atlantic surveys, 1998 (3). 1 records from Bay of Fundy Species List. 30 records from Mammal Records (West Wales). 94 records from SWFSC Marine Mammal Survey, Vaquita 1997, Cruise 1608. 1 records from Données naturalistes de Julien BIRARD. 2 records from Seabirds of the Southern and South Indian Ocean. 313 records from Observatoire Pelagis boat surveys 2003-2019. 216 records from PIROP Northwest Atlantic 1965-1992. 56 records from DUML New River surveys on the occurrence, distribution and density of marine mammals in Camp Lejeune 2010-2011. 3 records from AMAPPS Northeast Aerial Cruise Summer 2011. 8 records from Sightings for Airborne Mine Neutralization System Aerial Monitoring in the NSWC PCD Study Area from October 2011, 2012. 10 records from Argyll Biological Records Dataset. 142 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores tuna fishery from 1998 to 2013: while fishing. 57 records from DUML surveys for the stock discrimination of bottlenose dolphins along the Outer Banks of North Carolina 2011-2012. 9 records from UNCW JAX Aerial Survey - Right side - 2016. 3 records from Données naturalistes de Benoit FONTAINE. 28 records from Sightings for SSAM2-BOSS Sonar Test Event - June 2013. 52 records from Data collected on citizen science web portal www.ornitho.cat. 1 records from Collections and observation data National Museum of Natural History Luxembourg. 2 records from Lund Museum of Zoology (MZLU). 1 records from Colección de Mamíferos del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-M). 9 records from Dedicated boat-based surveys for marine megafauna in Suriname. 9 records from The Mammalia Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 37 records from Tasmanian Museum and Art Gallery provider for OZCAM. 3 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 7 records from SOCAL Marine Mammal Aerial Monitoring 2008-2009. 2 records from HRC Aerial Surveys Aug 20-22 2013. 3 records from CEN_PACA_2017_12_18. 90 records from Marybio Foundation marine mammal shipboard sightings in Bahia San Antonio, Patagonia 2008-2010. 12 records from Seatrust Cetacean Records West Wales. 35 records from AFTT JAX Aerial Survey -Left side- 2012-2013. 1 records from HRC CRC Small Vessel-Based Monitoring Surveys December 2009. 1264 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 1 records from MIRC NAVFAC Incidental Sightings - Vessel 1965-2014. 48 records from SEFSC GoMex Oceanic 1993 (S). 18 records from Paleobiology Database. 4 records from AMAPPS Northeast Aerial Cruise Spring 2017. 4 records from VACAPES PAX Vessel Opportunistic Sightings July 2015 - Nov 2017. 16 records from DUML coastal surveys on the occurrence, distribution and density of marine mammals in Camp Lejeune 2010-2013. 106 records from AMAPPS Southeast Aerial Cruise Summer 2010. 58 records from SWFSC Marine Mammal Survey, STAR 2000, Cruise 1616. 2 records from SWFSC Marine Mammal Survey, SWAPS 1997, Cruise 1607. 192 records from Cascadia Research Collective Hawaii OASIS project whale and dolphin sightings. 13 records from Copeland Island Bird Observatory SeaWatch Survey. 2033 records from Données du Réseau d'observateurs des mammifères marins en mer de la Manche. 1 records from New Zealand fish and squid distributions from research bottom trawls 1964-2008. 11 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Mamíferos marinos Chetumal). 27 records from MMS High Altitude Survey, SCB 1975-1978. 3 records from MIRC PIFSC CNMI Vessel Surveys Aug-Sep 2011. 6 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 13 records from University of Algarve and ICNB Cetacean Sightings 1999. 8 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 1 records from BoBO - Botanic Garden and Botanical Museum Berlin Observations. 3 records from JAX FIREX Aerial Surveys 5-8 September 2012. 18 records from UNCW Norfolk Canyon Aerial Survey - Right side - 2015. 17 records from DUML vessel-based photo-id and biopsy surveys in Onslow Bay CHPT OPAREA 2011-2015. 1 records from MIRC Saipan Marine Species Monitoring Winter-Spring Surveys 2012. 14 records from Observations de mammifères marins du Réseau National d'Echouages en Outre-Mer. 1 records from VACAPES MISSELEX Aerial Monitoring March 2013. 129 records from naturgucker. 21 records from Données d'observation des Marine Mammal Observers durant le levé sismique 3D SHELL en Guyane française en 2012 par Shell Exploration and Production France. 2 records from Animal Sound Archive. 8 records from Cetacean sightings in Ghana and Ivorycoast. 2 records from CUMV Mammal Collection. 10 records from Colección de Mastozoología. 3517 records from iNaturalist Research-grade Observations. 296 records from SEFSC GoMMAPPS 2018 Fall Aerial Survey. 1 records from Programme Ecoscope: données d'observations des écosystèmes marins exploités (Réunion). 1293 records from Inventaire des Mammifères marins de France (métropole et outre-mer). 198 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 2 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 313 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2018. 25 records from AMAPPS Northeast Shipboard Cruise Spring 2014. 110 records from Actualización de la base de datos del Atlas Mastozoológico de México. 200 records from Mammal collection of National Museum of Nature and Science. 259 records from Visual sightings from Song of the Whale 1993-2013. 10 records from Hatteras Eddy Cruise 2004. 1 records from Atlas of Life in the Coastal Wilderness. 88 records from AMAPPS Southeast Aerial Cruise Winter 2019-2020. 1 records from Visual contacts from research cruises in the Med sea, 1994-2001. 3 records from Mammals on map of Ukraine. Materials of the First Ukrainian Mammal Mapping Conference. 8 records from Bahamas Marine Mammal Research Organisation Aerial Survey. 5 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 2 records from Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 1 records from Macalester College marine mammal sightings around Grenada, West Indies 1999. 8 records from Reef Life Survey: Global reef fish dataset. 21 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 4 records from SWFSC Marine Mammal Survey, ORCAWALE 2008, Cruise 1635. 3 records from Étude sur les Mammifères marins de Mayotte entre 2004 et 2008 par l'ONCFS Mayotte, la Collectivité Départementale de Mayotte/Direction de l'Environnement et du Développement Durable, l'Université de la Rochelle et la DAF Mayotte. 202 records from Observations issues des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) en 2011 et 2012. 36 records from AFTT JAX Aerial Survey -Right side- 2012-2013. 389 records from Natural History Museum Rotterdam - Specimens. 2 records from Mammals Specimens. 14 records from SWFSC Marine Mammal Survey, CCES 2018, Cruise 1651. 2 records from BOEM Sperm Whale Seismic Study (SWSS) MPS cetacean sightings 2002-2004. 19 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 1 records from Auswildlife. 42 records from Northern Territory Museum and Art Gallery provider for OZCAM. 4 records from MIRC NAVFAC MISTCS Vessel Surveys Jan-Apr 2007. 18 records from SOCAL Marine Mammal Aerial Monitoring 2010. 3 records from Mammifères de France métropolitaine. 53 records from AMAPPS Southeast Aerial Cruise Winter 2013. 1 records from Formación de las colecciones de referencia de aves y mamíferos de la Reserva de la Biosfera de Sian Ka'an, Quintana Roo, México. 2 records from JAX MAVEX September 2012. 10 records from Sightings from R/V Song of the Whale during the winter 2019 MAPS survey (NMFS permit 14809). 3 records from NEFSC Survey 1997. 118 records from GVI Mexico Coral Reef Monitoring. 30 records from Empire Wind Digital Aerial Wildlife Surveys for BOEM Lease Area OCS-A 0520, Equinor Wind US LLC, November 2017-October 2018. 4 records from UAM Mammal Collection (Arctos). 5 records from Marybio Foundation marine mammal aerial sightings in Bahia San Antonio, Patagonia 2008-2010. 3515 records from Marine mammal monitoring from coastal sites in Cardigan Bay, UK, 2004-2009. 77 records from Norfolk/VA Beach MINEX Vessel Surveys. 25 records from AFTT JAX Aerial Survey -Left side- 2014. 1 records from Glasgow Museums BRC: Mammals. 7 records from HRC KB22 Searcher Vessel Survey Feb 2014. 30 records from AFTT Cape Hatteras Aerial Survey -Right side- 2014. 3 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 2 records from Données naturalistes de Patrick HAFFNER. 39 records from NEFSC Aerial Survey - Summer 1998. 55 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 168 records from Marine mammal sightings off Galápagos. 1 records from Tour_du_Valat_2017_12_18. 1 records from List of Cetacean Species in Vava'u. 1 records from HRC Koa Kai-11 Marine Species Monitoring Aerial Surveys November 2010. 9 records from UNCW JAX Aerial Survey -Right side- 2017. 5 records from CRC HRC PMRF Small Vessel-Based Monitoring Surveys February 2016. 156 records from National Mammal Atlas Project, online recording. 26 records from SEFSC Gomex Shelf 1998. 7 records from CRC HRC PMRF Small Vessel-Based Monitoring Surveys February 2015. 36 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 15 records from Records of protected animals species in Ukraine. 11 records from NBIS Records to December 2016. 6 records from Merseyside BioBank (unverified). 18 records from Department of Agriculture Environment and Rural Affairs (DAERA) Marine and Fisheries Division Marine Survey Data. 8 records from CRC HRC PMRF Small Vessel-Based Monitoring Surveys February 2014. 7 records from Ireland's BioBlitz. 22 records from CODA cetacean sightings on primary platform of vessel surveys 2007. 852 records from Observatoire des Mammifères marins de l'Archipel Guadeloupéen. Suivi Dauphins Les Saintes. 2 records from UAZ Mammals. 69 records from AMAPPS Southeast Aerial Cruise Fall 2017. 21 records from Cetacean coordinated transborder monitoring using ferries as platforms of observation off Tunisia 2013-2014 - Atutax. 1 records from Acoustic Detections for Airborne Mine Neutralization System Passive Acoustic Monitoring in the NSWC PCD Study Area from December 2011. 1 records from AMAPPS Northeast Aerial Cruise Winter 2014. 1 records from Dr Mary Gillham Archive Project. 4 records from Sightings for AN/AQS-20 Sonar Test Event - December 2013. 1 records from Seabird and cetacean sightings from Cruise SY002 of RV Shoyo Maru, Tropical Atlantic Ocean, Oct. 2000. 3 records from UNCW PAX Aerial Survey - Right side - 2016. 323 records from Bottlenose dolphins off Outer Banks 2007-2012. 13 records from SEFSC GoMex Oceanic 2001. 360 records from Ecological Baseline Studies of the U.S. Outer Continental Shelf Option Year 1. 135 records from AMAPPS Southeast Aerial Cruise Spring 2019. 89 records from Observations naturalistes des Amis de BioObs.. 25 records from SOCAL FZN4 Marine Mammal Aerial Monitoring 2013. 2 records from Kenneth S. Norris Center for Natural History, University of California, Santa Cruz (UCSC) Mammal specimens (Arctos). 48 records from SEFSC GoMex Oceanic 1992 (199). 3 records from Opportunistic records of marine megafauna in Suriname. 65 records from AMAPPS Southeast Aerial Cruise Winter 2015. 2 records from SEWBReC Mammals (South East Wales). 35 records from NCSM Mammalogy Collection. 525 records from Ecology of Lahille's bottlenose dolphin Tursiops truncatus gephyreus in the Patos Lagoon estuary and adjacent marine coast. 28 records from USWTR JAX Aerial Survey -Right side- 2010-2011. 70 records from SWFSC Marine Mammal Survey, CADDIS 1995, Cruise 1601. 1 records from MIRC NAVFAC Incidental Sightings - Shore 1965-2014. 1 records from UNCW PAX Aerial Survey - Right side - 2017. 209 records from Données d'occurrence de mammifères marins des campagnes REMMOA - Observatoire PELAGIS UMS 3462 et Agence des aires marines protégées. 5 records from UNCW PAX Aerial Survey - Right side - 2015. 5 records from Naturalis Biodiversity Center (NL) - Paleontology. 1 records from Vertebrate fossil collection of National Museum of Nature and Science. 5 records from Observations cétacés Martinique 2013/2014. 61 records from DUML vessel-based photo-id and biopsy surveys for proposed JAX USWTR site 2012-2015. 4 records from HRC CRC Small Vessel-Based Monitoring Surveys November-December 2006. 18 records from Cetacean coordinated transborder monitoring using ferries as platforms of observation off Tunisia 2013-2014 - Ketos. 15 records from NEFSC Survey 1998 2. 32 records from Royal Belgian Institute of Natural Sciences Mammal collection. 46 records from SEFSC Mid-Atlantic Tursiops Survey, 1995 (1). 57 records from Données d'occurrence du dispositif Megascope - Observatoire PELAGIS UMS 3462. 32 records from RBINS DaRWIN. 8 records from Fife Nature Records Centre combined dataset. 110 records from Natural History Museum (London) Collection Specimens. 440 records from Norfolk/VA Beach Inshore Vessel Surveys. 1 records from Avistamientos de fauna en el Distrito Nacional de Manejo Integrado Yuruparí. 2 records from Queen Victoria Museum Art Gallery provider for OZCAM. 30 records from SWFSC Marine Mammal Survey, MOPS 1990, Cruise 1370. 17 records from Virginia CZM Wind Energy Area Survey - Left side - May 2014 through December 2014. 2 records from Programme Ecoscope: données d'observations des écosystèmes marins exploités. 4 records from CRC HRC Small Vessel-Based Monitoring Surveys January 2012. 1 records from Ulster Wildlife Living Seas Marine Species Records. 37 records from Virginia CZM Wind Energy Area Survey - Right side - May 2014 through December 2014. 172 records from SEFSC GoMMAPPS 2018 Winter Aerial Survey. 92 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 63 records from AMAPPS Southeast Aerial Cruise Spring 2014. 10 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2015. 124 records from AMAPPS Southeast Aerial Cruise Fall 2012. 249 records from OMMAG_Données de 2008 à 2015. 2443 records from SEFSC Dolphin Photo ID. 1 records from Institut Mediterrani d'estudis Avançats (CSIC-UIB): IMEDEA-VERT. 32 records from SEFSC GoMex Oceanic 1999. 50 records from CAS Mammalogy (MAM). 1 records from HRC KB26 Shoreline Aerial Surveys Jan-Feb 2014. 4 records from Observations de mammifères marins dans les Iles Éparses - Observatoire PELAGIS. 44 records from SWFSC Marine Mammal Survey, MOPS 1989, Cruise 1267. 7 records from UNCW JAX Aerial Survey - Right side - 2015. 5 records from National Museums Scotland marine strandings Z.2014.21. 75 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 18 records from SEFSC GoMMAPPS Vessel Survey 2017 Summer. 32 records from AFTT JAX Aerial Survey -Right side- 2014. 29 records from USWTR JAX Aerial Survey -Left side- 2011-2012. 1 records from RV Investigator Voyage IN2016_T02 Seabird Observations, Australia (2016). 38 records from Sightings for AN/AQS-20 Sonar Aerial Monitoring in the NSWC PCD Study Area from July 2011 and May 2012. 66 records from SWFSC Marine Mammal Survey, STAR 1999, Cruise 1613. 5 records from Inventaire des oiseaux et des mammifères marins réalisé dans la ZEE de Guyane française en 2011-2012. GEPOG & RN du Grand Connétable. 19 records from Vertebrates (except birds, INNS and restricted records), Outer Hebrides. 25 records from UNCW USWTR JAX Aerial Surveys May - Oct 2010 - Left side. 174 records from Bottlenose Dolphin Research Institute (BDRI) cetacean sightings 2011. 2 records from CRC HRC PMRF Aerial Ship-follow Surveys February 2015 and 2016. 8 records from Observations des cétacés des campagnes européennes SCAN2 et CODA - Observatoire PELAGIS. 6 records from Colección osteológica de mastozoología marina. 59 records from SWFSC Marine Mammal Survey, STAR 1999, Cruise 1614. 998 records from Christopher Newport University bottlenose dolphin sightings in Virginia estuaries 2000-2006. 69 records from AMAPPS Northeast Shipboard Cruise Summer 2013. 9 records from UNCW JAX Aerial Survey -Left side- 2017. 195 records from SEFSC Southeast Cetacean Aerial Survey 1992. 2 records from HRC Kaula Vessel-Based Monitoring Surveys June 2010. 6 records from HRC CRC Small Vessel-Based Monitoring Surveys May 2012. 61 records from CEDaR Online Recording. 33 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Mammalogy National Collection (MACNMa). 6 records from Museu Paraense Emílio Goeldi - Mastozoology Collection. 43 records from SEFSC GoMex Oceanic 1997. 2 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 15 records from SEFSC GoMex Oceanic 2000. 9 records from SA Fauna (BDBSA). 10 records from MMS Low Altitude Survey for Mammals, Southern California Bight 1975-1978. 1 records from Seasearch Marine Surveys in Scotland. 16 records from NEFSC Twin Otter Aerial Survey 2008. 3 records from AMAPPS Northeast Aerial Cruise Winter 2011. 66 records from Observatoire Pelagis sightings from fishery surveys 2004-2009. 1807 records from NMNH_material_samples. 1 records from Mammal collection of Biodiversity Center of Japan, Ministry of the Environment (BDCJ). 1 records from California State University, Long Beach Mammals. 2 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from CSIRO, Rachel Cruises, Shark Data, Arafura Sea, North Australia, 1984. 6 records from KUBI Mammalogy Collection. 1 records from HRC USWEX Aerial-based Shoreline Surveys February and March 2011. 326 records from Observations opportunistes de mammifères marins de l'observatoire PELAGIS. 3 records from SEFSC Caribbean Survey 1995. 62 records from Aerial Survey Baseline Monitoring in the Continental Shelf Region of the VACAPES OPAREA: January 2016 - December 2016 (left side). 8072 records from NOAA Atlantic bottlenose dolphin sightings in the coastal and estuarine waters near Charleston, SC - 1994-2011. 2 records from (UTC) University of Tennessee Mammals Collection. 4 records from University of Michigan Museum of Zoology, Division of Mammals. 5 records from Atlas of Danish Mammals. 5 records from VACAPES FIREX Aerial Monitoring 2011. 2163 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores tuna fishery from 1998 on: during navigation or search mode. 94 records from AMAPPS Southeast Aerial Cruise Summer 2011. 1 records from Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 32 records from USWTR JAX Aerial Survey -Right side- 2011-2012. 64 records from SWFSC Marine Mammal Survey, STAR 2003, Cruise 1623. 285 records from South Australian Museum Australia provider for OZCAM. 2 records from Cetacean Sightings Survey and Southern Ocean Cetacean Program - BROKE-West. 5 records from Observations de cétacés de la campagne aérienne ATLANCET - Observatoire PELAGIS. 2 records from Seasearch Marine Surveys in Ireland. 1 records from DMNS Mammal Collection (Arctos). 103 records from DOF - Observations from the Danish Ornithological Society. 6 records from An Extended dataset of registration points of species listed in Resolution 6 and 4 of the Bern Convention. 3 records from HRC CRC Small Vessel-Based Monitoring Surveys April-May 2009. 1 records from NEFSC Aerial Circle-Back Abundance Survey 2006. 3 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 59 records from HBRG Vertebrates (not Badger) Dataset. 14 records from AFAST Hatteras Aerial Survey -Left side- 2011-2012. 849 records from UNCW Marine Mammal Aerial Surveys 2006-2007. 1 records from Gomex Sperm Whale Survey 2000. 3 records from National Museum of Natural Science. 2 records from HRC Kaula Vessel-Based Monitoring Surveys July 2012. 2 records from HRC Vessel-Based Monitoring Surveys February 2011. 5 records from CRC HRC PMRF Small Vessel-Based Monitoring Surveys August 2017. 55 records from SWFSC Marine Mammal Survey, PODS 1992, Cruise 1467. 14 records from SCANS II cetacean sightings from aerial surveys 2005. 4 records from Avistamiento de fauna marina desde la embarcación en la Expedición de Montes Submarinos 2021. 84 records from AMAPPS Northeast Shipboard Cruise Summer 2011. 21 records from SEFSC GoMex Oceanic 1994. 42 records from SWFSC Marine Mammal Survey, Delphinus 2009, Cruise 1640. 1 records from ISM Mammalogy Collection. 484 records from Marine Mammal and Sea Turtle Sightings in the Vicinity of the Maryland Wind Energy Area 2013-2015. 1 records from MCP-Mamiferos - Coleção de Mamíferos. 58 records from SWFSC Marine Mammal Survey, STAR 1998, Cruise 1611. 104 records from SEFSC Gomex Shelf 2001. 1 records from Données d'observation opportunistes collectées par la Réserve Naturelle Nationale de l'Ile du Grand-Connétable et le Groupe d'Etude et de Protection des Oiseaux en Guyane. 116 records from Naturalis Biodiversity Center (NL) - Mammalia. 1 records from JAX MISSILEX Aerial Monitoring 2010. 202 records from DUML vessel-based photo-id and biopsy surveys in VACAPES OPAREA off Hatteras 2009, 2011-2015. 21 records from UNCW Hatteras Aerial Survey -Left side- 2017. 11 records from UNCW Norfolk Canyon Aerial Survey -Right side- 2017. 1 records from HRC Vessel Survey off Kaua'i, January 2012. 125 records from AMAPPS Southeast Aerial Cruise Spring 2017. 1 records from Mammal Mapper App Sighting Records. 25 records from AMAPPS Northeast Aerial Cruise Summer 2016. 88 records from DFO Maritimes Region Cetacean Sightings. 6 records from JAX MAVEX Aerial Monitoring 2012. 41 records from SBMNH Vertebrate Zoology. 17 records from Données d'observations de cétacés par le Groupe d'étude des Cétacés de Méditerranée (GECEM) de 2009 à 2012. 80 records from UK Royal Navy Marine Mammal Observations. 1 records from Biodiversitätsdatenbank Salzburg. 19 records from NEFSC Aerial Survey - Summer 1995. 5 records from SEFSC GoMex Oceanic 1993 (W). 1003 records from Community structure and abundance of bottlenose dolphins Tursiops truncatus in coastal waters of the northeast Gulf of Mexico. 4 records from Census of the threatened species of Benin.. 1 records from HRC CRC Small Vessel-Based Monitoring Surveys October 2010. 19 records from SEFSC Caribbean Survey 2000. 86 records from AMAPPS Southeast Aerial Cruise Winter 2011. 1 records from MIRC KB17 Vessel Surveys Mar 2012. 2 records from BOEM Sperm Whale Seismic Study (SWSS) S-Tag cetacean sightings 2005. 393 records from United Kingdom National Whale Stranding Database 1913-2008. 4 records from MSB Mammal Collection (Arctos). 30 records from Consolidación y sistematización de las colecciones de referencia de peces y mamíferos marinos del ITESM Campus Guaymas. 188 records from SWFSC Marine Mammal Survey, STAR 1998, Cruise 1612. 11845 records from NMNH Extant Specimen Records. 8 records from Registros de peces y cetaceos en el marco del proyecto Ocurrencia, distribución, estado genético y de contaminantes de los cetáceos de La Guajira. 1 records from Inventario de aves y mamíferos en humedales de Laguna de Términos y Pantanos de Centla en Tabasco y Campeche. 29 records from Observations des cétacés de la campagne européenne SCAN3 - Observatoire PELAGIS. 76 records from Museums Victoria provider for OZCAM. 33 records from Earth Guardians Weekly Feed. 1 records from Collection Mammalogie - ZSRO. 12 records from Cetacean distribution in the South Atlantic and South Pacific Ocean (AR-OBIS). 25 records from DUML vessel-based surveys for proposed JAX USWTR site 2009-2011. 13 records from Marine biological observation data from coastal and offshore surveys around New Zealand. 1 records from HRC Koa Kai-11 Marine Species Monitoring Vessel Surveys November 2010. 15 records from UMZC Zoological Specimens. 24 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Unassessed data. 4 records from Reef Life Survey - Survey Records. 24 records from SWFSC Marine Mammal Survey, MOPS 1988, Cruise 1165. 14 records from Population status of small cetaceans off Aragua, Central Coast of Venezuela 2009. 9 records from Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 1 records from Comunidad íctica de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 13 records from Lamont-Doherty/LGL/NSF cruises. 17 records from Biodiversity4all Research-Grade Observations. 3 records from HRC SCC Aerial-Based Monitoring Survey February 2010. 50 records from USWTR JAX Aerial Survey -Right side- 2009-2010. 4 records from UWBM Mammalogy Collection (Arctos). 35 records from Happywhale - Common Bottlenose Dolphin in South Atlantic Ocean. 5 records from Mystic Aquarium's marine mammal and sea turtle stranding data 1976-2011. 10 records from Mammalogie ZMK. 4 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 1 records from Clare Biological Records Centre Dataset 2004-2007. 9 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 15 records from Registros de especies priorizadas de mamíferos de Colombia, recopilados a partir de la información de fototrampeo. 8 records from Cetacean survey in Balabac Strait, Philippines. 27 records from NHMD Mammalogy Collection. 15 records from UNCW USWTR JAX Aerial Surveys May - Oct 2010 - Right side. 43 records from National Trust for Scotland Species Records. 38 records from Sightings from R/V Song of the Whale during the spring 2019 MAPS survey (NMFS permit 14809). 15 records from NEFSC North Atlantic Marine Mammal and Turtle Aerial Abundance Survey 2007. 9 records from Données Nord-Pas-de-Calais. CMNF. 75 records from ecoscope_observation_database. 5 records from UNCW PAX Aerial Survey - Left side - 2017. 1 records from Creación de la base de datos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, y de la reserva de la biosfera Islas del Golfo de California para el grupo de los mamíferos. 2 records from UNCW PAX Aerial Survey - Left side - 2015. 5 records from Protected species bycatch in New Zealand fisheries. 97 records from Isle of Wight Notable Species. 86 records from Données observation à bord d'un ferry de Mammifères marins ORCA. 1 records from HRC CETOS Vessel-Based Monitoring Surveys January 2007. 1 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 59 records from Observations de cétacés à partir de navires de pêches: campagnes PETRACET/PROCET et OBSMAM - Observatoire PELAGIS. 4 records from NatureServe Network Species Occurrence Data. 1 records from Mammals housed at MHNG, Geneva. 32 records from ALA species sightings and OzAtlas. 5 records from HRC CRC Small Vessel-Based Monitoring Surveys October-November 2011. 14 records from Ocean Genome Legacy Collection. 2 records from Mammal osteology MZS. 9209 records from WDC Shorewatch Sightings. 1 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Mamíferos San cristóbal). 1 records from Bycatch along Romanian Black Sea coasts 2010-2011. 6 records from Sightings for REMUS Sonar Test Event - July 2013. 4 records from Cetaceans sighted off the west coast of the South Island, New Zealand, Summer 1970. 1206 records from Azorean Biodiversity Portal. 3 records from Cetacean sightings along the catalan coast. 13944 records from Observations du Grand dauphin du Golfe normand-breton. 184 records from Data on cetacean occurrence collected during the project “Identification and initial assessment of cetacean groupings in coastal waters of the north-western Black Sea, Ukrainian sector” funded by ACCOBAMS 2016-2017. 73 records from Diversidad, distribución y abundancia de cetáceos en Bahía de los Ángeles y Canal de Ballenas, Golfo de California: bases científicas para una nueva área de observación turística de mamíferos marinos. 31 records from Cybelle Méditerranée. Observation nautique ponctuelle. 105 records from SWFSC Marine Mammal Survey, STAR 2000, Cruise 1615. 18 records from SWFSC Marine Mammal Survey, CAMMS 1991, Cruise 1426. 80 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 15 records from HRC CRC Small Vessel-Based Monitoring Surveys July-August 2010. 54 records from Suivi aérien des mammifères marins dans le périmètre du Parc naturel marin d'Iroise en 2010. 1 records from Australian Museum Factsheets. 13 records from SEUS Right Whale EWS Aerial Surveys 2016-17. 26 records from Field Museum of Natural History (Zoology) Mammal Collection. 10 records from UNCW Norfolk Canyon Aerial Survey - Right side - 2016. 15 records from AMAPPS Northeast Aerial Cruise Fall 2012. 47 records from Collection Anatomie Histologie - SMF. 22 records from SEFSC GoMMAPPS Vessel Survey 2018 Winter. 2 records from HRC CRC Small Vessel-Based Monitoring Surveys April 2010. 974 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 1 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 40 records from SWFSC Marine Mammal Survey, MOPS 1988, Cruise 1164. 4 records from AMAPPS Northeast Aerial Cruise Fall 2019. 11 records from SWFSC Marine Mammal Survey, ORCAWALE 2001, Cruise 1617. 69 records from SWFSC Marine Mammal Survey, MOPS 1986, Cruise 0989. 1 records from Condrictios del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 321 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2017. 1 records from RV Investigator Voyage IN2016_V06 Seabird Observations, Australia (2016). 265 records from Victorian Biodiversity Atlas. 83 records from Données d'occurrence Espèces issues de la base Natura 2000 : espèces d'intérêt communautaire et autres espèces remarquables renseignées dans les FSD. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences